Physicochemical properties of new imidazolium-based ionic liquids containing aromatic group - Kermanioryani, M. (American Chemical Society, 2016)
In this work, three novel imidazolium-based ionic liquids containing aromatic group in the cation combined with bis(trifluoromethylsulfonyl)imide anion were synthesized and characterized. Their thermophysical properties namely, density, viscosity, thermal decomposition, glass transition, and heat capacity were measured at various temperatures and atmospheric pressure. In addition, physicochemical properties such as molar volume (Vm) and crystal energy (UPOT) were also determined from the obtained density data. Novel group contribution parameters were obtained using Gardas and Coutinho model aiming at providing simple method to predict density and viscosity of ionic liquids. Â© 2016 American Chemical Society.